Mental fatigue and soccer: Current knowledge and future directions - Smith, M. R.; Thompson, C.; Marcora, S. M.; Skorski, S.; Meyer, T.; Coutts, A. J. (Sports Medicine, 2018)
Fatigue is a complex state with multiple physiological and psychological origins. However, fatigue in soccer has traditionally been investigated from a physiological perspective, with little emphasis on the cognitive demands of competition. These cognitive demands may induce mental fatigue, which could contribute to the fatigue-related performance decrements observed during and after soccer matches. Recent research investigating the relationship between mental fatigue and soccer-specific performance supports this suggestion. This leading article provides an overview of the research in this emerging field, outlining the impact of mental fatigue on soccer-specific physical, technical, decision-making, and tactical performances. The second half of this review provides directions for future research in response to the limitations of the existing research. Emphasis is placed on translating the current body of knowledge into practical applications and developing a greater understanding of the mechanisms underpinning the negative impact of mental fatigue on soccer performance. A conceptual model is presented to help direct this future research.